La littérature est la mort du langage - Krzykawski, Michał (Romanica Silesiana)
Michał Krzykawski investigates the works by Bataille and Sollers, showing paradoxes of dialectic relationships between the literature and the language. Keywords : Bataille; Sollers; the death of language; literature; eroticism